DIAGNOSTIC ACCURACY OF MODIFIED EARLY OBSTETRIC WARNING SYSTEM FOR PREDICTION OF MATERNAL MORBIDITY - Zohra, Sadaf; Urooj, Uzma; Khalid, Nayla; Khan, Sumaira; Siraj, Asifa; Rana, Munawar Jannat (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the diagnostic accuracy of modified early obstetric warning system for predicting maternal morbidity keeping ICU admission as “gold standard”. Study Design: Cross sectional validation study. Place and Duration of Study: Department of Obstetrics and Gynecology, Pak Emirates Military Hospital, Rawalpindi, from Oct 2018 to Apr 2019. Methodology: A total of 205 patients of singleton pregnancy, post-natal period <6 weeks, history of hypertension and diabetes were considered in the study. Women were followed up to 6 weeks for maternal morbidity in term of intensive care admission. All the data regarding findings of Modified early obstetric warning system and intensive care admission was noted. Results: The age range of patients was 18-40 years with mean age of 31.585 ± 3.31 years, mean gestational age was 37.595 ± 1.84 weeks and mean parity was 1.839 ± 1.59. Modified early obstetrics warning system as shown sensitivity of 84.38%, specificity 97.11%, diagnostic accuracy by 95%, positive predictive value of 84.38%, negative predictive value of 97.11%, (p=0.001) for prediction of maternal morbidity. Conclusion: Modified early obstetrics warning system chart fulfills most of criteria of ideal screening tool making it a significant bedside screening tool which can predict obstetric morbidity and mortality in pregnant patients.